Adsorption of Chromium (III) Solution Using Calcium Hydroxyapatite - Promsorn, Thanya; Songsasen, Apisit; Wannalerse, Boontana (RMUTP Research Journal Sciences and Technology, 2021)
Chromium (III) is an inorganic salt being used as corrosion inhibitor, plating agents, surface treating agents, furniture, furnishings, and textile printing, and etc. The discharge of industrial waste water containing chromium (III) into the water source was toxic to the aquatic lives, and some parts accumulate in the soil, chromium (III) reduces the growth of plants, reduced photosynthesis, inhibit the enzyme activity, imbalanced in plants, and reduced productivity, and etc. For this reason, method to remove it before discharge the effluent into the water source is necessary. The use of apatite materials for adsorption, and immobilization of various pollutants was a technique that was more likely to be used. Due to its high adsorbency, easy to use, and environmentally friendly. The purpose of this research was to study the preparation of calcium hydroxyapatite, structural characterization of calcium hydroxyapatite by X-ray diffraction technique, adsorption study of chromium solution with calcium hydroxyapatite in various conditions, and the determination of adsorption isotherm. The results showed that the optimum contact time of calcium hydroxyapatite and chromium solution was 3 hours. Most adsorption works well at a pH of around 6.76. Considering the amount of chromium (III) adsorbed at equilibrium (q), it was found that the calcium hydroxyapatite with 10 % zinc added that has been calcined to 400 OC, and the calcium hydroxyapatite with 15 % zinc added that has been calcined to 800 OC were to adsorb chromium (III) more than other sorbents. The adsorption isotherm was suited with Fruendlich and Langmuir. The calcium hydroxyapatite with 10 %, and 15 % zinc added that has been calcined to 400 OC had the highest adsorption capacity (qm) up to 178.57, and 181.82 mg/g respectively. In addition, it was found that calcium hydroxyapatite, which heated to 800 degrees Celsius, can decompose tricalciumphosphate.